ОБЗОР ЛИТЕРАТУРЫ О ВЛИЯНИИ РАЗЛИЧНЫХ ГАЗОВ НА ЛЕГКИЕ ЧЕЛОВЕКА - Рахмонбердиев Муҳаммаджон Ахмаджон ўғли (TADQIQOTLAR, 2025)
Abstract. Exposure of the lungs to airborne toxicants from different sources in the  environment  may  lead  to  acute  and  chronic  pulmonary  or  even  systemic inflammation. Cigarette smoke is the leading cause of chronic obstructive pulmonary disease,  although  wood  smoke  in  urban  areas  of  underdeveloped  countries  is  now recognized as a leading cause of respiratory disease. Mycotoxins from fungal spores pose an occupational risk for respiratory illness and also present a health hazard to those living in damp buildings. Microscopic airborne particulates of asbestos and silica (from building materials) and those of heavy metals (from paint) are additional sources of indoor air pollution that contributes to respiratory illness and is known to cause respiratory illness in experimental animals. Ricin in aerosolized form is a potential bioweapon  that  is  extremely  toxic  yet  relatively  easy  to  produce.  Although  the aforementioned  agents  belong  to  different  classes  of  toxic  chemicals,  their pathogenicity is similar. They induce the recruitment and activation of macrophages, activation of mitogen-activated protein kinases, inhibition of protein synthesis, and production of interleukin-1 beta. Targeting either macrophages (using nanoparticles) or the production of interleukin-1 beta (using inhibitors against protein kinases, NOD-like receptor protein-3, or P2X7) may potentially be employed to treat these types of lung  inflammation  without  affecting  the  natural  immune  response  to  bacterial infections.